Mediator role of metacognition in the relationship between nicotine addiction and emotion dysregulation in adult smokers - Tunç, Pervin; Çağlın, Duygu; Ülgen, Margörit Rita Krespi (Journal of Dependence, 2025)
Objective: Examining the psychological factors underlying nicotine addiction seems important in understanding the maintenance of addiction. This study examined the association between severity of nicotine addiction, difficulties in emotion regulation (DER) and metacognitive beliefs (MCBs). Method: The sample consisted of 255 people at the age of 18 and over, smoking at least one cigarette daily. The data were collected online by using the Turkish versions of Fagerström Test for Nicotine Dependence, Difficulties in Emotion Regulation Scale-Short Form, Metacognitions About Smoking Questionnaire, and Demographic Information Form. Results: A significant positive relationship was found between daily cigarette consumption and the severity of nicotine addiction. Among difficulties in emotion regulation, nonacceptance emerged as a significant predictor. Additionally, both positive metacognitive beliefs related to cognitive regulation and negative metacognitive beliefs regarding uncontrollability significantly predicted nicotine dependence. Findings also showed that metacognitive beliefs had a mediating role in the relationship between difficulties in emotion regulation and addiction severity. While the initial model accounted for 40% of the variance, the inclusion of metacognitive beliefs increased the explained variance to 58%, underscoring their substantial explanatory power. Conclusion: The substantial increase in the expained variance reflects the strong explanatory contribution of metacognitive beliefs in understanding the severity of nicotine addiction.